2015
DOI: 10.5007/2177-5230.2015v30n60p109
|View full text |Cite
|
Sign up to set email alerts
|

O Furacão Catarina e a Floresta Ombrófila Mista no Parque Nacional de Aparados da Serra, sul do Brasil

Abstract: A região sul do Brasil foi atingida em março de 2004 pelo Furacão Catarina que causou queda de árvores pelos fortes ventos. Para avaliar a influência do furacão foram amostrados os indivíduos arbóreos em 100 parcelas contíguas de 10 x 10m, demarcadas na Floresta Ombrófila Mista Altomontana do Parque Nacional de Aparados da Serra, localizado na região Sul do Brasil. Dos indivíduos amostrados no levantamento, 5% foram tombados pelos ventos do furacão. A altura média das árvores caídas foi de 8 m, variando entre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Because of the geographical and climatic conditions, this forest formation has unique characteristics in the PNAS region, and this forest is preserved and also related to the richness of existing epiphytes (IBAMA, 2004). Santos et al (2015) highlighted that the forest in the PNAS is characterized with the emerging crowns of the araucaria, and confirmed that the canopy is formed mainly by species of Myrtaceae, Lauraceae and Aquifoliaceae. Furthermore, Bergamin (2010) pointed out that the Podocarpus lambertii is scarce.…”
Section: Study Areamentioning
confidence: 60%
“…Because of the geographical and climatic conditions, this forest formation has unique characteristics in the PNAS region, and this forest is preserved and also related to the richness of existing epiphytes (IBAMA, 2004). Santos et al (2015) highlighted that the forest in the PNAS is characterized with the emerging crowns of the araucaria, and confirmed that the canopy is formed mainly by species of Myrtaceae, Lauraceae and Aquifoliaceae. Furthermore, Bergamin (2010) pointed out that the Podocarpus lambertii is scarce.…”
Section: Study Areamentioning
confidence: 60%
“…In the study area, the formation of large clearings was observed, which included sample plots, at the time of the survey carried out in 2016. Santos et al (2015), analyzing the influence of the passage of a hurricane in Mixed Ombrophilous Forest at the National Park of Aparados da Serra, southern of Brazil, also observed that there were changes in the structure of the tree community.…”
Section: Horizontal Structural Dynamicsmentioning
confidence: 93%
“…In just one southern Brazilian state, Santa Catarina, 45 extreme atmospheric events like cyclones and waterspouts were registered between 1976 and 2003 (Marcelino et al 2009), including more recent cyclone events in 2009, 2019, and 2020. As cyclones were historically rare disturbances in this region, their impacts on the forest and how plant communities recover from these events are poorly known, despite some previous works addressing it (Beckert et al 2014;Santos et al 2015;Liebsch et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This vegetation covers large areas in south and Southeastern Brazil, mainly in high and cold plateaus (Duarte et al 2014;Kersten et al 2015;Rezende et al 2015), and it has been dramatically fragmented in recent years due to the expansion of planted forests and agriculture. Despite some studies addressing the effects of cyclones over treebreaking patterns and survival probabilities in the Araucaria Forest (Beckert et al 2014;Santos et al 2015), community-level analyses and interspecific variation are poorly documented.…”
Section: Introductionmentioning
confidence: 99%